PROFIL PENGUASAN BAHASA KOMBAI - Buha Aritonang (SAWERIGADING, 2012)
Kombai language is spoken by Kombai ethnic in Kombai village, Kouh, Boven Digoul, West Papua. This research is an associative research and the objective of this research is to determine the relationship between independent and dependent variables. In this case, it contents of the relationship between Kombai respondents characteristic and mastery of Kombai language. Independent variables consist offour parts, gender variables (X1), age groups (X2), educational levels (X3), and occupation (X4). Dependent variable is mastery of Kombai language. This research uses descriptive and Crosstabs analysis that determine the relationship and closeness of independent and dependent variables. The result of four hypotheses, it can be concluded that there is not a relationship between X1, X2, X4 and Y. Meanwhile, there is a relationship between X3 and Y. The closeness of the variables [(X1 and Y), (X2 and Y), (X3 and Y), and (X4 and Y)] are weak and grades of variables are not more than 1. Abstrak Bahasa Kombai dituturkan oleh suku Kombai di Kampung Kombai, Kouh, Boven Digoul, Papua Barat. Penelitian ini adalah penelitian asosiatif dan tujuan penelitian ini untuk mengetahui hubungan antara variabel independen dan dependen. Dalam hal ini, penelitian ini menitikberatkan hubungan antara karakteristik responden Kombai dan penguasaan bahasa Kombai. Variabel independen terdiri atas empat bagian, yaitu jenis kelamin (X1), kelompok usia (X2), tingkat pendidikan (X3), dan pekerjaan (X4). Sementara itu, varibel dependen adalah penguasaan bahasa Kombai (Y). Penelitian ini menggunakan analisis deskriptif dan Crosstabs untuk mengetahui hubungan dan keeratan variabel independen dan dependen. Hasil empat hipotesis menyimpulkan bahwa tidak ada hubungan antara variabel X1, X2, X4 dan Y. Sementara itu, ada hubungan antara X3 dan Y. Keeratan variabel tersebut [(X1 and Y), (X2 and Y), (X3 and Y), and (X4 and Y)] lemah dan nilai variabelnya di bawah angka 1.